![2\ln(x+3)=0\implies \ln(x+3)^2=0\implies e^{\ln(x+3)^2}=e^0\implies (x+3)^2=1](https://tex.z-dn.net/?f=2%5Cln%28x%2B3%29%3D0%5Cimplies%20%5Cln%28x%2B3%29%5E2%3D0%5Cimplies%20e%5E%7B%5Cln%28x%2B3%29%5E2%7D%3De%5E0%5Cimplies%20%28x%2B3%29%5E2%3D1)
Expanding the left side gives
![x^2+6x+9=1\implies x^2+6x+8=0\implies (x+4)(x+2)=0](https://tex.z-dn.net/?f=x%5E2%2B6x%2B9%3D1%5Cimplies%20x%5E2%2B6x%2B8%3D0%5Cimplies%20%28x%2B4%29%28x%2B2%29%3D0)
which gives two solutions,
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
and
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
. But if
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
, then
![\ln(x+3)=\ln(-1)](https://tex.z-dn.net/?f=%5Cln%28x%2B3%29%3D%5Cln%28-1%29)
, but this number isn't real, so
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
is an extraneous solution. Meanwhile if
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
, you get
![\ln(-2+3)=\ln1=0](https://tex.z-dn.net/?f=%5Cln%28-2%2B3%29%3D%5Cln1%3D0)
, so this solution is correct.
"Potential solutions" might refer to both possibilities, but there is only one actual (real) solution.